Patterning and Development of Photoreceptors in the Human Retina - Hussey, Katarzyna A.; Hadyniak, Sarah E.; Johnston, Robert J. (Frontiers in Cell and Developmental Biology, 2022)
Humans rely on visual cues to navigate the world around them. Vision begins with the detection of light by photoreceptor cells in the retina, a light-sensitive tissue located at the back of the eye. Photoreceptor types are defined by morphology, gene expression, light sensitivity, and function. Rod photoreceptors function in low-light vision and motion detection, and cone photoreceptors are responsible for high-acuity daytime and trichromatic color vision. In this review, we discuss the generation, development, and patterning of photoreceptors in the human retina. We describe our current understanding of how photoreceptors are patterned in concentric regions. We conclude with insights into mechanisms of photoreceptor differentiation drawn from studies of model organisms and human retinal organoids.